2022
DOI: 10.1182/bloodadvances.2021004992
|View full text |Cite
|
Sign up to set email alerts
|

Clonal phylogeny and evolution of critical cytogenetic aberrations in multiple myeloma at single-cell level by QM-FISH

Abstract: Single-cell analysis is of significant importance in delineating the exact phylogeny of the subclonal population and in discovering subtle diversification. So far, studies of intratumor heterogeneity and clonal evolution in multiple myeloma (MM) were largely focused on the bulk tumor population level. We performed quantitative multigene fluorescence in situ hybridization (QM-FISH) in 129 longitudinal samples of 57 MM patients. All the patients had newly diagnosed and relapsed paired samples. An expanded cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…Consistent with previous findings, 19,21 we found an increase in 1q copy number from diagnosis to relapse in a significant proportion of gain(1q)-positive tumors. A progression from 3 copies to ≥4 copies of 1q21, which has been recently associated with poor outcome, 19 was observed in 16/148 (11%) cases (Table S4). Additionally, an amp (1q) clone was acquired in seven patients who had 2 copies of 1q at first presentation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous findings, 19,21 we found an increase in 1q copy number from diagnosis to relapse in a significant proportion of gain(1q)-positive tumors. A progression from 3 copies to ≥4 copies of 1q21, which has been recently associated with poor outcome, 19 was observed in 16/148 (11%) cases (Table S4). Additionally, an amp (1q) clone was acquired in seven patients who had 2 copies of 1q at first presentation.…”
Section: Discussionsupporting
confidence: 92%
“…In our cohort, similar to other reports, 35,36 we observed an increase in high‐risk CAs from presentation to relapse. The most commonly gained CAs at relapse were del(17p) and gain/amp(1q) in 13% and 12% of cases, respectively, in agreement with the literature (8–23% and 13–19% of cases, respectively) 19,21,28,37 . However, if only the first relapse is considered, the percentages might be lower.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The development of MM has been classically viewed as a multistage process ( 4 ). However, the common initiating events, including multiple cytogenetic aberrant, with immunoglobulin heavy chain translocation and hyperdiploidy are insufficient to cause MM occurrence, as MGUS/SMM patients commonly harbor these abnormalities and show no clinical symptoms of MM ( 5 , 6 ). Intra-clonal heterogeneity has been observed at all stages of MM.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that the evolution of cytogenetic aberrations over time has prognostic significance in MM [ 51 , 52 , 53 ]. Recently, Yan et al performed a single-cell analysis using quantitative multi-gene FISH on 129 longitudinally sampled specimens from 57 MM patients confirming that patients with stable cytogenetic structure achieve significantly longer survival than patients with evolutionary dynamics [ 54 ]. In our dataset, we identified only two patients (7%) with a stable CNV profile ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%